DEVELOPMENT OF E-LKPD BASED ON SOCIO-SCIENTIFIC ISSUES ON LEARNING MATERIALS TO IMPROVE STUDENTS' CRITICAL THINKING - Godlif Sianipar; Mhd Riza Marjoni; Ratna Ayu Pawestri Kusuma Dewi; Regina Yoantika Natalie; Mardiati Mardiati (Sean Institute, 2023)
Student worksheets are printed worksheets that are frequently used in classrooms. The effectiveness of LKPD in online learning is lower. Similar improvements have been made in science and technology, as well as in the context of the process of learning to adapt to the COVID-19 pandemic. This necessitates creating LKPD that is more creative and can be presented in an electronic student worksheet (E-LKPD) format for use online. Electronic Student Worksheets are online learning resources that are methodically organized into specific instructional units and delivered in electronic format. By examining the appropriateness of the media, teacher reactions, and the efficacy of employing teaching materials, this research intends to offer electronic student worksheet products based on socio-scientific issues in learning materials to increase students' critical thinking. The ADDIE technique, which stands for analysis, design, development, implementation, and evaluation, is the development approach used. The findings of the study on the creation of the e-LKPD demonstrate the viability of e-LKPD media based on socio-scientific issues in instructional materials to enhance students' critical thinking, with 93 percent falling into the highly viability group. So that the e-LKPD that has been developed is declared suitable for use as a support for the learning process.